State of the art on the agent of citrus psorosis disease - Milne R.G. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
Recent results and insights on the probable causal virus of citrus psorosis disease are summarized. Symptoms can include ringspots, and the best characterized isolate is known as citrus ringspot virus; however, we use the alternative name citrus psorosis-associated virus CPSaV) to avoid confusion with other ringspot virus diseases of citrus. CPSaV is a multicomponent ssRNA virus with a coat protein (CP) of 48-50K. The rodshaped 'spirovirus' particles described earlier are collapsed duplex forms of the circles. Two other viruses with some similar properties have recently been described: ranunculus white mottle from Italy and tulip mild mottle mosaic from Japan, with CPs of 43 and 46 K respectively. A new genus Ophiovirus has been proposed for the three viruses. Regarding diagnostic, partial sequences of an isolate of CPSaV have been reported, together with the use of PCR primers based of them. A DAS-ELISA is currently being employed to detect psorosis in some citrus orchards and nurseries in Southern Italy.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)